(3QHj GdTGajs - (3GOGf, YGFTIs; (3GdZGfe, MhQs; (3YcGhj, QMGHs; (3cfYGf, CMeOs ((3GdOGQ GdHjVGA, GdeZQHs (3OGQ GdKbGaI ddfTQ hGdJhRjYs, 2024)
(3Gddg gh GdPj jTaj LejY GdeQVi aj gPG GdYGde(B. (3hGddg gh GdPj jefM GdTaGA dLejY GdeQVi(B. (3GSe Gddg (B"(3GdTGaj(B" (3jYfj Cfg jTajfG hjefMfG GdTaGAs
(3JQHjI OjfjIs
Keywords: (3GdOjfs